1999
DOI: 10.1007/s004250050593
|View full text |Cite
|
Sign up to set email alerts
|

Particle-bombardment-mediated co-transformation of elite Chinese rice cultivars with genes conferring resistance to bacterial blight and sap-sucking insect pests

Abstract: Transgenic rice plants were generated using particle bombardment to simultaneously introduce the rice Xa21 gene eective against bacterial blight and the Galanthus nivalis agglutinin (snowdrop lectin; gna) gene eective against sap-sucking insect pests, speci®cally the brown plant hopper. Using three plasmids, we cotransformed 5-to 10-d-old, mature seed-derived rice (Oryza sativa L.) callus of two elite Chinese rice cultivars, Eyi 105 and Ewan 5. The plasmids carried a total of four genes. The gna and Xa21 genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(39 citation statements)
references
References 71 publications
3
35
0
1
Order By: Relevance
“…The transformed leaf discs developed into the callus and then the shoots were emerged with in 18-22 days. Accumulating evidences suggested that in vitro tissue culture and micro propagation are necessary for transformation experiments to remodel the aesthetic and growth characteristics of the plants (Jaime and Teixeira, 2003;Siemens and Schieder, 1996;Tang et al 1999). The roots continued to grow in the putative transgenic plants on rooting medium.…”
Section: Resultsmentioning
confidence: 99%
“…The transformed leaf discs developed into the callus and then the shoots were emerged with in 18-22 days. Accumulating evidences suggested that in vitro tissue culture and micro propagation are necessary for transformation experiments to remodel the aesthetic and growth characteristics of the plants (Jaime and Teixeira, 2003;Siemens and Schieder, 1996;Tang et al 1999). The roots continued to grow in the putative transgenic plants on rooting medium.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, provision of low concentrations (0.2-1.6 mL L -1 ) of squirting cucumber fruit juice was found efficient for kanamycin-resistant callus and shoot regeneration without any bacterial overgrowth in the culture medium. Results emphasized the importance of modification of the regeneration protocol along with transformation experiments in order to achieve desirable characteristics (Siemens and Schieder, 1996;Tang et al, 1999;Jaime and Teixeira, 2003;Bakhsh et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Our long-term goals are to improve the quality of rice by using an approach in which multiple disease-and insect-resistant traits can be introduced into the same lines [2]. In our experiment, the insecticidal activity of transgenic rice plants on LF and SSB wereinvestigated (Tab 4 and Tab 5).…”
Section: Insecticidal Activity Of T 1 Transgenic Plantsmentioning
confidence: 99%
“…Although a decade ago rice was considered as one of the most recalcitrant crops in terms of genetic manipulation, it has recently emerged as the model cereal for the study of plant genomics, plant pathology, gene regulation and expression, metabolic pathway manipulation and the inheritance, organization, rearrangement and fate of transgenes [1], [2]. Remarkable progress has been made in the development of systems for Agrobacterium tumefaciences -mediated transformation in rice since 1994 [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%